Manufacturing Pluralism in Brazilian Economics. Issue 3 (3rd July 2019) - Fernandez, Ramón Garcia; Suprinyak, Carlos Eduardo
Abstract: Contrary to the situation prevailing in most of Europe and North America, Brazilian economics can be justly described as pluralist, an outcome frequently ascribed to the role played by the Brazilian economics association (ANPEC) as conflict mediator. A crucial episode took place in the early 1970s, when ANPEC chose to welcome the filiation of the heterodox program at the University of Campinas (Unicamp) against threats of withdrawal from one of its most prestigious members, the Getúlio Vargas Foundation. After characterizing the nature of pluralism in current Brazilian economics, the article uncovers the process that led ANPEC to adopt a "pluralist" attitude, and how this related to the Brazilian political context from the 1970s. The outcome was significantly influenced by the actions of other institutions involved in Brazilian economics at the time, notably the Ford Foundation and the team of Vanderbilt University economists working in Brazil under a USAID contract. Choices made within a delicate political context opened the door to the institutionalization of theoretical plurality as a stable feature of the scholarly community of Brazilian economists.